Debunking Divine Command Theory - Hans Van Eyghen (Religions, 2023)
The divine command theory holds that morality finds its origin in God or that God is somehow closely connected to morality. Many people across the world hold a related, though different belief that Religious belief is required for proper moral behavior. In this paper, I look at a number of evolutionary and cognitive explanations (supernatural punishment theory, big gods theory, moral dyad, and costly signaling) that purport to explain why people hold beliefs concerning a close connection between God and morality. I assess whether any of these theories provide a reason for epistemic concern.